Radiologic Features and Prognosis of Gastric Perforation - Putra, I Putu Aryana Kusuma; Inayah Wulandari; Shira Shalsabina Shafitri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Gastric perforation carries high rates of morbidity and mortality, making it a critical surgical emergency. This systematic review presents recent evidence of radiological imaging, including its evaluation for the diagnosis of gastric perforation and its effect on patient prognosis. The search strategy included an extensive literature review from online databases, including PubMed and Google Scholar, with key phrases (such as